Properties of Recycled Concrete Aggregate - Ibrahim, Ahmad J. (Al-Mukhtar Journal of Sciences, 2010)
Five grades of concrete mixes where designed and produced with natural aggregate. After tested at the age of 28 days, these concretes in the form of cast cubes, prisms and cylinders where crushed and screened to produce recycled concrete aggregates with similar grading of original one, then the physical and mechanical properties of coarse and fine recycled aggregate have been studied comparing with natural original aggregate. Tests on the aggregates showed, that recycled concrete aggregate gave lower specific gravity and higher water absorption capacity than the original aggregate. The resistance to mechanical action such as impact, crushing, and abrasion for the coarse recycled aggregate is also lower. The properties of recycled aggregate are not significantly affected by the mechanical properties of the original concrete.